Public Universities Fees Hike in Nigeria: Reasons, Social Implications and Suggestions for Decision Making for Effective University Administration in Nigeria - OGUNODE, Niyi Jacob; ODANWU, Gladys Nkiruka (Researchparks Publishing, 2023)
The paper discussed the social implications of fees hike in public universities in Nigeria. Secondary data were used in the paper. The data were collected from both print and online publications. The paper submitted that stakeholders in tertiary education especially the universities have made their position known on the fee hike in Nigerian universities. Stakeholders like the National Association of Nigerian Students (NANS) and the Academic Staff Union of Nigerians Universities have opposed the idea of university fees hike and advised the government not to increase the fees in the various universities. Also, the paper in the areas of reasons given by universities in Nigeria for the fess increment identified; increment in cost of administration, low subvention from the government and poor internally generated revenue. On the social implications of fee hikes in Nigeria, the paper identified a likely reduction in university enrolment, retention and graduate output, an increment in the prostitution rate among female students, an increment in criminal activities, insecurity problems and poor human capital development. The paper concluded that the suggestions of the government on fees increment to enable public universities to generate more revenue and to be able to contribute to the internal management of the various universities is a welcome idea. But increment in the fees of various universities with the present economic challenges of inflation and high poverty rate and without any social programme designed or put in place to reduce the impacts of fees hike on the students and parents is not the best decision. Based on this, the paper hereby recommended that the federal and state government should launch a bursary and scholarship programme for students in tertiary institutions across the country. Private institutions and religious organizations should be encouraged to commence scholarship programmes for students. Fees increment in any university should be agreed upon by the stakeholders in various universities before implementation. The government should implement 15-20% budget allocation to education of as recommended by UNESCO.